Collateral resistance to taxanes in enzalutamide‐resistant prostate cancer through aberrant androgen receptor and its variants. Issue 10 (28th August 2018) - Shiota, Masaki; Dejima, Takashi; Yamamoto, Yoshiaki; Takeuchi, Ario; Imada, Kenjiro; Kashiwagi, Eiji; Inokuchi, Junichi; Tatsugami, Katsunori; Kajioka, Shunichi; Uchiumi, Takeshi; Eto, Masatoshi
Abstract : Currently, the optimal sequential use of androgen receptor (AR) axis‐targeted agents and taxane chemotherapies remains undetermined. We aimed to elucidate the resistance status between taxanes and enzalutamide, and the functional role of the AR axis. Enzalutamide‐resistant 22Rv1 cells showed collateral resistance to taxanes, including docetaxel and cabazitaxel. However, taxane‐resistant cells showed no collateral resistance to enzalutamide; taxane‐resistant cells expressed comparable protein levels of full‐length AR and AR variants. Knockdown of both full‐length AR and AR variants rendered cells sensitive to taxanes, whereas knockdown of AR variants sensitized cells to enzalutamide, but not to taxanes. In contrast, overexpression of full‐length AR rendered cells resistant to taxanes. Consistently, the prostate‐specific antigen response and progression‐free survival in docetaxel chemotherapy were worse in cases with prior use of ARAT agents compared with cases without. Collateral resistance to taxanes was evident after obtaining enzalutamide resistance, and aberrant AR signaling might be involved in taxane resistance. Abstract : Enzalutamide‐resistant cells showed collateral resistance to taxanes, but not vice versa; androgen receptor was involved in resistance to enzalutamide as well as taxanes. As a result, patient prognosis following treatment with docetaxel was worse in cases with prior use of androgen receptor axis‐targeted agents.